Polycrystalline SnO2 films grown by chemical vapor deposition on quartz glass. (December 2015) - Lu, Y.M.; Jiang, J.; Becker, M.; Kramm, B.; Chen, L.; Polity, A.; He, Y.B.; Klar, P.J.; Meyer, B.K.
Abstract: Tin dioxide (SnO2 ) thin films were deposited on quartz glass substrates by chemical vapor deposition using SnI2 and O2 as reactants. The growth experiments were carried out in the substrate temperature range of 300–900 °C. X-ray diffraction, scanning electron microscopy, X-ray photoelectron spectroscopy, spectrophotometry and Raman spectroscopy were used to characterize the films. The films were polycrystalline with their crystallites having a preferred orientation, which was dependent on the film thickness. The average grain size increased with increasing thickness of the films. The binding energies of Sn 3d5/2 and O 1s for all samples showed the Sn 4+ and O-Sn 4+ bonding state from SnO2 . The absolute average transmittance of SnO2 films exceeded 90% in the visible and infrared range. The obtained SnO2 films had optical band gaps between 3.78 and 3.92 eV. Highlights: SnI2 (Sn 2+ ) was used as the Sn precursor to prepare tin oxide films by CVD. Pure-phase SnO2 ﬁlms were grown on quartz glass in the temperature range of 350–900 °C. Microstructures in terms of grain orientation, size and shape, depend on the film thickness. Novel arrow-shaped grains and faceted surface were observed for films grown at 650 °C. Films have optical band-gaps (3.78–3.92 eV) in line with that of single-crystal SnO2 .